2019
DOI: 10.1055/s-0039-1697970
|View full text |Cite
|
Sign up to set email alerts
|

Encondromas da mão: Uma experiência de 20 anos

Abstract: Objective  Enchondromas are the commonest tumors of the bones of the hand. Treatment approaches vary. The present article presents the characteristics of the tumors, diagnostic methods, and treatments. Methods  We discuss the approach used in our institution, where we have treated 48 patients with enchondromas of the hand between 1996 and 2016. Our technique of treatment, which has remained the same over 2 decades, comprises the use of curettage, high-speed burr, and autologous bone graft (harvested with a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(52 reference statements)
2
7
0
Order By: Relevance
“…The findings of our study are largely consistent with those of previous studies [1][2][3][4][15][16][17]. In most patients, enchondromas were diagnosed in the third and fourth decades of life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of our study are largely consistent with those of previous studies [1][2][3][4][15][16][17]. In most patients, enchondromas were diagnosed in the third and fourth decades of life.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, 48 patients with an enchondroma located in the hand were treated with an autologous bone graft, which was harvested from the iliac bone crest via a minimally invasive technique (using a Craig biopsy needle). The authors did not find any complications in the donor site [16]. In our study, minor complications, such as donor site pain or related thigh numbness and superficial infection, were observed in five patients (20,83%), which were related to the donor site (iliac crest bone graft harvested using the conventional technique).…”
Section: Discussionmentioning
confidence: 45%
“…►Table 3 shows the comparison of our reported results with other studies in the literature reporting on more than 20 cases of surgical management of enchondroma. 10,12,[14][15][16][17][18][19][20][21][22][23][24][25][26] The distribution of lesions in our study correlates to the previous experience in the literature demonstrating both a preponderance for the ulnar digits and for the proximal phalanges. 27 However, while the results of Gaulke suggest this difference is significant and cannot be attributed to chance, there does not appear to be an accepted explanation or mechanism by which this occurs.…”
Section: Discussionsupporting
confidence: 87%
“…Table 3 shows the comparison of our reported results with other studies in the literature reporting on more than 20 cases of surgical management of enchondroma. 10 12 14 15 16 17 18 19 20 21 22 23 24 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Bierry et al [3] study showed that enchondromas in children appear as relatively large lesions. Sollaci et al [5] are reporting their 20 years' experience in their institute and found that the size of the tumors ranged from 0.2 cm 2 to 5.7 cm2, with a mean size of 1.7 cm2 (SD ¼ 1.0 cm 2 ). [5] Other studies by Pandey [6] and Ambulgekar et al [4] reported large enchondromas presented with and without pathological fracture respectively.…”
Section: Case Presentationmentioning
confidence: 99%